1994
DOI: 10.1152/ajpheart.1994.266.5.h1854
|View full text |Cite
|
Sign up to set email alerts
|

Calcium is involved in both positive and negative modulation of the secretory system for ANP

Abstract: The calcium dependence of the atrial natriuretic peptide (ANP) secretory system is controversial. Some studies clearly support a stimulatory role, whereas others favor an inhibitory role for calcium in this endocrine system. We demonstrate that calcium is involved in both a positive modulatory role and a negative modulatory role, thereby providing some explanation for the seemingly irreconcilable findings previously published. The negative modulatory role performed by calcium is evident during basal secretion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Thapsigargin, which inhibits sarcoplasmic reticulum calcium adenosine triphosphate and depletes intracellular calcium stores, does not alter basal ANP secretion but blocks stretch induced ANP release [75]. Based on their experiments in cultured rat atrial myocytes, Doubell and Thibault [76] postulated that calcium has a negative effect on ANP secretion under basal conditions but a positive modulatory role under conditions of stimulated sustained release. Calcium depletion has been shown to decrease the stimulation of ANP secretion by phenylepherine and endothelin [54,77] in cultured myocytes but also attenuated the ANP inhibitory response to C-type natriuretic peptide and cGMP in vitro [44].…”
Section: Cellular Mechanisms For Anp Secretionmentioning
confidence: 99%
“…Thapsigargin, which inhibits sarcoplasmic reticulum calcium adenosine triphosphate and depletes intracellular calcium stores, does not alter basal ANP secretion but blocks stretch induced ANP release [75]. Based on their experiments in cultured rat atrial myocytes, Doubell and Thibault [76] postulated that calcium has a negative effect on ANP secretion under basal conditions but a positive modulatory role under conditions of stimulated sustained release. Calcium depletion has been shown to decrease the stimulation of ANP secretion by phenylepherine and endothelin [54,77] in cultured myocytes but also attenuated the ANP inhibitory response to C-type natriuretic peptide and cGMP in vitro [44].…”
Section: Cellular Mechanisms For Anp Secretionmentioning
confidence: 99%
“…The concept of basal release has been difficult to equate with what is known concerning the action of secretagogues and the secretory granule population. If it is independent of the constitutive route, it also has major differences from regulated release, not least in that calcium has a negative modulatory role (Doubell and Thibault, 1994). Given these discrepancies, it seems unlikely that the constitutive route could represent a secondary pool of ANP as considered here, although in its favour is the fact that fusion of small constitutive vesicles would not necessarily be seen using our ultrastructural assay.…”
Section: Are There Two Pools Of Anp?mentioning
confidence: 87%
“…The presence of two pools, a stretch-activated, regulated granule pool and a secondary, secretagogue activated pool, could help explain many of the apparent discrepancies in the literature on ANP release, in particular the complex role of calcium (Matsubara et al, 1988;De Bold and De Bold, 1989;Page et al, 1990Page et al, , 1991Doubell and Thibault, 1994). By altering the extracellular calcium concentration of cultured cardiac cells, it has been found that in low concentrations KC1 does not increase ANP secretion above basal levels, while the stimulatory effects of phenylephrine and endothelin are only partially diminished (Sei and Glembotoski, 1990).…”
Section: Are There Two Pools Of Anp?mentioning
confidence: 99%
“…In addition, in SR, the calsequestrin contains high acidic residues, which are the candidate for Ca binding [6], and Ca2+-ATPase is located on the membrane. Also, the ASG may contain prohormone [22], which could bind Ca with its high acidic portion [5,21]. In this respect ASG is also similar to SR.…”
Section: Discussionmentioning
confidence: 99%